Normas e princípios aplicáveis ao contrato internacional de trabalho - Thomaz, Sandra Regina (2013)
We chose the theme of this dissertation in order to point out the possible legal rules to be applied to international contracts of work, based on the sources of international, European Union and domestic law.Our choice is due to topicality and increasing labor relations at an international level, arising from the globalization of the economy and the formation of regional blocks, which allowed the movement of people across borders for the exercise of professional activities. We will approach the trajectory of international labor law and labor law in Brazil, an analysis of the principles that guide them to, then, move on to study the characteristics of international contracts of work and finally the international legal system regarding global, regional (European union and Mercosur) and Brazilian contexts, which can be used to resolve any disputes between employee and employer, when the relationship is made up of an international element